2020
DOI: 10.1080/13854046.2020.1722244
|View full text |Cite
|
Sign up to set email alerts
|

American Academy of Clinical Neuropsychology consensus conference statement on uniform labeling of performance test scores

Abstract: Objectives: Descriptive labels of performance test scores are a critical component of communicating outcomes of neuropsychological and psychological evaluations. Yet, no universally accepted system exists for assigning qualitative descriptors to scores in specific ranges. In addition, the definition and use of the term "impairment" lacks specificity and consensus. Consequently, test score labels and the denotation of impairment are inconsistently applied by clinicians, creating confusion among consumers of neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
115
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(122 citation statements)
references
References 17 publications
1
115
0
6
Order By: Relevance
“…The classification of test performance carried out in the group of older adults using the framework by Guilmette and co-authors ( Guilmette et al, 2020 ) revealed that the majority (∼85%) of test scores was “ within normal limits ,” with a further ∼10% of “ low average ,” ∼5% “ below low average ” and less than 1% “ exceptionally low ” scores. This was consistent with rates expected in healthy controls assessed with a multi-test battery ( Axelrod and Wall, 2007 ; Binder et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The classification of test performance carried out in the group of older adults using the framework by Guilmette and co-authors ( Guilmette et al, 2020 ) revealed that the majority (∼85%) of test scores was “ within normal limits ,” with a further ∼10% of “ low average ,” ∼5% “ below low average ” and less than 1% “ exceptionally low ” scores. This was consistent with rates expected in healthy controls assessed with a multi-test battery ( Axelrod and Wall, 2007 ; Binder et al, 2009 ).…”
Section: Resultsmentioning
confidence: 99%
“…Of the two groups, particular care was taken to evaluate diagnostic statuses in the group of older adults, since in this age range prevalence of cognitive impairment is estimated to range between 5% and 40% ( Pais et al, 2020 ). To assess their cognitive profile the diagnostic labelling consensus proposed by the American Academy of Clinical Neuropsychology was followed, whereby performance above the expected 24th percentile is considered within normal limits ( Guilmette et al, 2020 ). We thus used the entire cohort of ≥70 year-old adults ( n = 75) from which the study group of older adults had been extracted, to define numerical cut-offs corresponding to the 24th, 8th, and 2nd percentile for each test score.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We controlled the effects of the age or schooling in a separate analysis using multiple linear regression residuals when normative data covered only one of these variables. For each test, the function was categorized as preserved (z-score > −0.66), including average, high average, above average, and exceptionally high scores), low average score (z-score between −0.7 and −1.26); below-average score (z-score between −1.32 and −1.82); and exceptionally low score (z-score < −1.96) (Beauchamp et al, 2015; Guilmette et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Analyses focused on rates of low test performance using a < −1 SD cutoff. Descriptors applied in clinical practice, including the recently published American Academy of Clinical Neuropsychology Consensus Statement (Guilmette et al, 2020), often include several descriptor categories to indicate degree of departure from average performance. Our focus on a < −1 SD cutoff captures all performances below that cutoff together, thus collapsing across several descriptor categories.…”
Section: Methodsmentioning
confidence: 99%